SYNTHESIS THE DIGITAL REGULATORS OF LOWERED ORDER FOR THE RESERVED SYSTEMS MANAGEMENT BY CONTINUOUS OBJECTS - Zimchuk, I. V. (Radio Electronics, Computer Science, Control, 2018)
Context. Complication of digital regulator of the closed control systems by the continuous objects is determined by the dimension of mathematical model of control object, which given as a transmission function. In practice more preferable are simple regulators a dimension of which is a less dimension of object. For this reason a task of synthesis the control system with use the linear regulators of subzero order is the article attention of many researchers. Objective. Exposition the results of development methodology by synthesis of digital regulators the lowered order with the assured control quality on the basis of reduction transmission function of control object. Method. Simplification of regulators is arrived at by using for the synthesis the reduction transmission function of control object. A synthesis it is suggested to execute in two stages. On the first stage reduction of transmission function of management object comes true. The criterion quality of reduction is accordance the values of integral estimations quality of transient initial and simplified models the management objects reserved by the single negative feed-back of the automatic control system. The quality criterion is arrived at by providing the accordance of indirect indexes quality of transient initial and reduction models. On the second stage the direct synthesis of digital regulator will be realized. The use of synthesis method of compensative regulators is in-process shown. Results. Application of the expounded approach is shown on the example of synthesis the digital regulator for FLL system. Work example and simulation results are presented. Conclusions. Unlike the known approaches, accordance between initial and simplified transmission functions arrived at by the appropriation to reduction model the values of indirect indexes quality of initial model transient, which are determined on frequency descriptions. Practical meaningfulness of work consists in creation the methodology synthesis of simple linear digital regulators for reserved control system continuous objects.